2015
DOI: 10.1186/s12889-015-2499-2
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of colorectal cancer education: a randomized trial of health fairs

Abstract: BackgroundRegular screening for colorectal cancer (CRC) reduces morbidity and mortality from this disease. A number of factors play a role in the underutilization of CRC screening; populations with the lowest CRC screening rates are least likely to be aware of the need for screening or have knowledge about screening options. The overall purpose of this project was to assess two methods for increasing knowledge about CRC in a health fair context: one, by using a health educator to provide CRC information at a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Generalizability may thus be limited, especially with regard to our documented interaction effects. While a prior study has shown greater increases in CRC knowledge among participants who took part in an inflatable colon tour compared to participants who did not, (Briant et al 2015) a randomized control trial with a control group would provide further insight as to whether it was the inflatable colon, or simply the provision of information that was associated with increased knowledge as well as intention to discuss and intention to screen for CRC. Further, comparative effectiveness research approaches may be helpful to determine the additive value of the inflated colon relative to simpler, more traditional interventions.…”
Section: Discussionmentioning
confidence: 95%
“…Generalizability may thus be limited, especially with regard to our documented interaction effects. While a prior study has shown greater increases in CRC knowledge among participants who took part in an inflatable colon tour compared to participants who did not, (Briant et al 2015) a randomized control trial with a control group would provide further insight as to whether it was the inflatable colon, or simply the provision of information that was associated with increased knowledge as well as intention to discuss and intention to screen for CRC. Further, comparative effectiveness research approaches may be helpful to determine the additive value of the inflated colon relative to simpler, more traditional interventions.…”
Section: Discussionmentioning
confidence: 95%
“…Education programs for lifestyle improvements should be conducted to reduce the incidence of colorectal cancer [36]. It has been suggested as an effective way to raise awareness, knowledge, and screening rate for colorectal cancer screening [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…Alternately, an example of inappropriate continuation of nonevidence-based programs is the continued use of health fairs for community screenings, interventions and education. While they may help increase visibility of services to subsets of the community, there is limited evidence that they increase screening follow-up, enhance sustained health knowledge, or improve health outcomes (13,14). Previous studies have suggested that between 58% and 62% of public health programs are evidence-based (15,16).…”
Section: Introductionmentioning
confidence: 99%